Marketing plan of online master degree based on Internet self-media for golden company after the epidemic - Lu Yang (2023)
Given the fact that international degree education is notorious in the Chinese market. Therefore, there is an urgent need to conduct an in-depth study on the marketing strtegy of international degree education. Based on marketing theory, this project mainly adopts literature research method, SWOT analysis method and the method of combining theory and practice. This this project analyses the current situation of the development of online master's degree in gold enterprises, gradually analyses the reasons, combines the PEST theory and Porter's five forces model, and analyses the macro-environment, industry environment and micro-environment of the development of the project from shallow to deep. Then, on the basis of SWOT analysis method, the current advantages and disadvantages, opportunities and threats are further analysed, so as to put forward specific suggestions for the marketing of Golden company online master degree project. After that, the smoothing index method, one-way linear regression method and Delphi method (expert scoring method) are applied to reasonably predict the sales of the online master's degree programme of the Golden Company in the next three years, and the 4P theory is applied to formulate practicable marketing measures in four aspects, namely, the product, the price, the channel and the marketing of the Golden Company online, in order to achieve the predicted marketing objectives.